Road to successful floriculture through soil micronutrient mapping of different zones of India - JHANJI, SHALINI; SHUKLA, A K; DHATT, K K; KUMAR, PRABHAT (The Indian Journal of Agricultural Sciences, 2021)
The present scenario for natural resource conservation demands for crop diversification and efficient management of natural resources, viz. water, nutrient, soil. The horticultural crops are always looked upon for diversification and within horticultural crops; fruits and vegetables are given prime importance for nutritional value and high outputs. Floricultural crops have emerged as potent livelihood crops for small and marginal farmers, employment for youth with low inputs, crop diversification and natural resource management. The improper use of inputs, viz. fertilizer and water in floral crops limits their production and can adversely affect soil health. So floriculturists should work on this least attended area and recommend appropriate fertilizers to flower growers for good quality production. In comparison to other crops, the nutrient requirement of floral crops is more due to which they scavenge more nutrients from soil so large amount of these nutrients are needed to replenish the soil to maintain balance. The critical limits of micronutrients for different agronomic crops have been developed and same are used for floricultural crops too but as requirement of these crops is higher so critical limits for floral crops need to be developed. Keeping in view all above, an attempt has been made to map micronutrient status of major flower producing states that could be used in management of micronutrient requirement of different floral crops. This will further help in development of policies pertaining to sound micronutrient management packages and precision fertilization in floriculture.